2001
DOI: 10.2135/cropsci2001.411149x
|View full text |Cite
|
Sign up to set email alerts
|

Summer and Autumn Growth of Rhizomatous Birdsfoot Trefoil

Abstract: A new population of birdsfoot trefoil (Lotus corniculatus L.) with rhizomes (RBFT) has been developed for greater persistence. No study has compared RBFT with a standard, non‐rhizomatous cultivar of birdsfoot trefoil (BFT). Objectives were to: (i) compare RBFT with BFT for differences in shoot and root mass and total nonstructural carbohydrate (TNC) concentration of taproots in both clipped and non‐clipped situations and (ii) describe rhizome production of clipped and non‐clipped RBFT. ‘Norcen’ BFT and RBFT we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
2
12
1
2
Order By: Relevance
“…2 and 3), a finding that concurs with previous works (Kallenbach et al 2001;Smith 1962;Striker et al 2008). This result indicates that carbon utilization from crown reserves allowed plants to compensate for leaf removal as seen in Medicago sativa cv.…”
Section: Crown Reserves and Plant Regrowth Under Defoliation And Floosupporting
confidence: 90%
See 1 more Smart Citation
“…2 and 3), a finding that concurs with previous works (Kallenbach et al 2001;Smith 1962;Striker et al 2008). This result indicates that carbon utilization from crown reserves allowed plants to compensate for leaf removal as seen in Medicago sativa cv.…”
Section: Crown Reserves and Plant Regrowth Under Defoliation And Floosupporting
confidence: 90%
“…In this respect, it was suggested that Lotus species are less dependent on crown reserves for regrowth than other forage legumes (i.e. alfalfa, Kallenbach et al 2001;Smith 1962). In this paper, we explore whether L. tenuis can intensively use reserves during regrowth when it is subjected to extreme carbon starvation caused by successive defoliations under flooding conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Marrocos and ARS 2620 rhizomatous genotypes registered the smallest DM yield in this study, agreeing with the results shown by Kallenbach et al (2001), who also related the small yileds of rhizomatous types of birdsfoot trefoil, and 50% inferior to the genotypes without rhizomes. Group 1 showed the best agronomic attributes due to its greatest regrowth dry matter yield and to the largest number of stems, showed by the genotypes under the shortest cutting interval.…”
Section: Resultssupporting
confidence: 92%
“…Poucos trabalhos têm sido conduzidos com estes genótipos, quanto à resposta a corte ou pastejo (Kallenbach et al, 2001). Na literatura nacional, não havia, até o desenvolvimento deste trabalho, quaisquer informações sobre a adaptação e a produção de forragem dos tipos rizomatosos.…”
Section: Introductionunclassified